Assuring the Quality of Achievement Standards and their Valid Assessment in Australian Higher Education. - Scott, Geoff (Office for Learning and Teaching, 2016)
Final report of a Teaching Fellowship at the Western Sydney University. The Fellowship explored the proposition that to assure the achievement standards and the quality of assessment in the contemporary university, it is necessary to first confirm the quality (relevance and desirability) of what is being assessed before looking at how well it is being assessed (for example, at confirming how 'fit-for-purpose' (valid) assessment tasks are, how reliable and well calibrated grading is, or how effectively plagiarism is being minimised). A complementary and equally important focus of the Fellowship was to identify what is necessary to build the capacity of those local leaders who are the key arbiters of whether any desired improvements in this area are effectively embraced, implemented and sustained – people in roles like Head of Program, School or Department, Associate Dean (Learning and Teaching), and Director of Learning and Teaching.